Developing learning professionals : integrating experiences in university and practice settings - Billett, Stephen; Henderson, Amanda (Springer, 2011)
In higher education institutions across the globe, there is a growing interest in integrating classroom learning with experience in practice settings. This interest is the result of an increased emphasis on courses that prepare students for specific occupations in the hopes that upon graduation students will be job-ready. Developing Learning Professionals: Integrating Experiences in University and Practice Settings explores how the integration of student experiences across university and practice settings might best be used to produce college graduates who are adept, critical practitioners.- Resumé vydavatel
Keywords: odborný výcvik; integrovaná výuka; vysoké školy; vocational education; integrated teaching; universities and colleges; elektronické knihy; sborníky; electronic books; papers of several authors